SPECIFIC ASPECTS OF FORMING THE CHARACTERISTICS OF SELF-MANAGEMENT OF PRIMARY SCHOOL STUDENTS - D. Saliyeva (Galaxy International Interdisciplinary Research Journal, 2022)
The article provides recommendations on teaching children of younger school age to plan in the formation of self-control characteristics, the formation of decisiveness, taking into account practical aspects.